A review of disaster mitigation analysis in learning - Tranggono, Mochamad Irvan; Sulindra, Gusti (Calamity: A Journal of Disaster Technology and Engineering, 2024)
Education has a role in building character and community disaster response through learning in schools. Learning that is integrated with disaster mitigation is one of the efforts to develop the soul (character) to have disaster preparedness. This is important to reduce the impact of the disaster. This study aims to present information related to disaster mitigation techniques on the lessons that have been carried out. through a literature review of 7 articles on the Google Scholar database with limitations for 2019-2023. The article search method begins with Harzing's publish or perish software. The results of the research based on the 7 articles that have been reviewed show that the integration of disaster preparedness learning towards disaster preparedness with various levels of education integrated into learning materials using a structured learning model and updates according to the year the journal was published.